Peritoneal dialysis-related peritonitis with an unexpected micro-organism: enterococcus hirae - BARUTÇU ATAŞ, DİLEK; AŞICIOĞLU, EBRU; VELİOĞLU, ARZU; TUĞLULAR, ZÜBEYDE SERHAN; ARIKAN, İZZET HAKKI (My University, 2017)
Enterococcus Hirae is a gram-positive, facultative, anaerobic bacterium which is usually a zoonotic pathogen rarely isolated from human infections. There are no published reports describing continuous ambulatory peritoneal dialysis (CAPD) related- peritonitis with Enterococcus Hirae in the literature. With the following report, we describe the case of peritoneal dialysis (PD)-related peritonitis due to Enterococcus Hirae.
Keywords: Enterococcus hirae; peritonitis; peritoneal dialysis